ANALYSIS OF FACTORS INFLUENCING THE READINESS OF ECONOMICS TEACHERS IN DIGITAL LITERACY-BASED LEARNING - Osisca, Ega; Nikensari, Sri Indah; Iranto, Dicky (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
Education is the foundation for societal progress, and in an increasingly advanced digital era, digital literacy has become an integral element in efforts to prepare future generations to face global challenges. In an educational unit, teacher’s someone who plays an important role in learning, so teachers must prepare themselves for digital literacy-based learning first. Several factors that influence teacher readiness in digital literacy-based learning are training, self-determination and reading intensity. This research aims to identify factors that influence teacher readiness in digital literacy-based learning. The research method using a quantitative approach use primary data with data collection technique in the form of questionnaires. Analysis was carried out using a multiple linear regression models with the SPSS 29.0 analysis tools. The results from this research shows that training, self-determination and reading intensity have a positive and significant effect on teacher readiness in digital literacy-based learning in the independent curriculum.